Attitudes towards the use of ict in costa rican university students: The influence of sex, academic performance, and training in technology - GARCÍA-MARTÍNEZ, JOSÉ ANTONIO (2021)
Information and communication technologies (ICT) are being used more and more as part of teaching processes in both formal and informal settings. In this regard, it is important to understand university students’ attitudes towards using ICT as they will shortly form part of the productive sector of society. The aim of this study was to analyze student attitudes during their final years pursuing various degrees at a university in Costa Rica. We used a non-experimental transactional design and probabilistic sampling that involved 1187 students. We used a questionnaire containing a Likert-type scales to measure attitudes, which was structured according to affective, cognitive, and behavioral components. The results showed positive attitudes in general, with higher scores in the cognitive and behavioral components, and moderate scores in the affective component. In addition, we found differences in attitudes according to sex, prior training in technology, and academic performance.